Human leucocyte antigens and mixed lymphocyte reaction in severe pre-eclampsia. - Jenkins, D M (1978)
Human leucocyte antigens (HLA) and mixed lymphocyte reactions (MLR) were studied in 38 women with severe pre-eclampsia and their husbands. Thirty-nine women with normal pregnancies and their husbands served as controls. Thirty-three of the control women were matched for age and parity with members of the study group. Infants were studied when possible. HLA compatibility was increased in the pre-eclamptic group compared with matched controls and with theoretical estimates for possible matings. The one-way MLR at delivery showed diminished response of maternal to paternal and cord cells in pre-eclamptic women. This reduced maternal reactivity in women with pre-eclampsia may have a role in the illness, and paternal/maternal histocompatibility may be a feature of the severe form.